Fighting over Meaning: Occupy Wall Street in American Mass Media and Occupiers’ Media - Saputra, Muhammad Beni (UI Scholars Hub, 2019)
In late 2011, Occupy Wall Street (OWS) grabbed the attention of American mass media. Media coverage on the anti-capitalist movement was mixed, some was positive and the majority was negative. Using Robert Entman’s framing theory, this paper provides a framing analysis of the OWS movement from mass media and occupiers’ media. Content analysis of news articles published by three different media platforms demonstrates that media framing of the OWS by both mass and occupiers’ media differs in terms of reporting and news focus. The difference results from the ideological streams of the three media in connection with respective political and socioeconomic interests. Despite the help of the internet that enables social movements to create alternative media for message distribution and follower mobilization, yet they are still lack of loyal fans and legitimacy. Nonetheless, alternative media such as that of the OWS are able to fight over meaning of social movement issues through the creation and dissemination of counter frames and disrupt the hegemonic power of mass media in framing social movements